K+ and pH homeostasis in the developing rat spinal cord is impaired by early postnatal X-irradiation - Syková, E; Jendelová, P; Simonová, Z; Chvátal, A (Brain research, 1992)
Activity-related transient changes in extracellular K+ concentration ([K+]e) and pH (pHe) were studied by means of ion-selective microelectrodes in neonatal rat spinal cords isolated from pups 2-14 days of age. Pups 1 to 2 days old were X-irradiated to impair gliogenesis and spinal cords were isolated 2-13 days postirradiation (PI). In 2- to 14-day-old pups PI stimulation produced ionic changes that were the same as those in 3- to 6-day-old control (non-irradiated) pups; e.g. the [K+]e increased by 4.03 +/- 0.24 mM (mean +/- S.E.M., n = 30) at a stimulation frequency of 10 Hz and this was accompanied by an alkaline shift of 0.048 +/- 0.004 pH units (mean +/- S.E.M., n = 32) pH units. By contrast, stimulation in non-irradiated 10- to 14-day-old pups produced smaller [K+]e changes, of 1.95 +/- 0.12 mM (mean +/- S.E.M., n = 30), and an acid shift of 0.035 +/- 0.003 pH units which was usually preceded by a scarcely discernible initial alkaline shift, as is also the case in adult rats. Our results show that the decrease in [K+]e ceiling level and the development of the acid shift in pHe are blocked by X-irradiation. Concomitantly, typical continuous development of GFAP-positive reaction was disrupted and densely stained astrocytes in gray matter of 10- to 14-day-old pups PI revealed astrogliosis. In control 3- to 6-day-old pups and in pups PI the stimulation-evoked alkaline, but not the acid, shift was blocked by Mg2+ and picrotoxin (10(-6) M). The acid shift was blocked, and the alkaline shift enhanced, by acetazolamide, Ba2+, amiloride and SITS. Application of GABA evoked an alkaline shift in the pHe baseline which was blocked by picrotoxin and in HEPES-buffered solution. By contrast, the stimulus-evoked alkaline shifts were enhanced in HEPES-buffered solutions. The results suggest a dual mechanism of the stimulus-evoked alkaline shifts. Firstly, the activation of GABA-gated anion (Cl-) channels induces a passive net efflux of bicarbonate, which may lead to a fall in neuronal intracellular pH and to a rise in the pHe. Secondly, bicarbonate independent alkaline shifts may arise from synaptic activity resulting in a flux of acid equivalents.
Keywords: neuroglie; draslík; Spinal Cord; Potassium; rentgenové záření; Immunoenzyme Techniques; Electric Stimulation; Neuroglia; novorozená zvířata; mícha; Ion Transport; krysa rodu Rattus; zvířata; Animals, Newborn; imunoenzymatické techniky; homeostáza; Astrocytes; Homeostasis; Hydrogen-Ion Concentration; Rats; iontový transport; X-Rays; Animals; elektrická stimulace; astrocyty; koncentrace vodíkových iontů